2020
DOI: 10.1001/jamainternmed.2020.0994
|View full text |Cite|
|
Sign up to set email alerts
|

Risk Factors Associated With Acute Respiratory Distress Syndrome and Death in Patients With Coronavirus Disease 2019 Pneumonia in Wuhan, China

Abstract: IMPORTANCE Coronavirus disease 2019 (COVID-19) is an emerging infectious disease that was first reported in Wuhan, China, and has subsequently spread worldwide. Risk factors for the clinical outcomes of COVID-19 pneumonia have not yet been well delineated.OBJECTIVE To describe the clinical characteristics and outcomes in patients with COVID-19 pneumonia who developed acute respiratory distress syndrome (ARDS) or died.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

510
7,394
83
428

Year Published

2020
2020
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 7,483 publications
(8,765 citation statements)
references
References 23 publications
510
7,394
83
428
Order By: Relevance
“…Increased case-fatality rates in the previously referenced analysis of 44,672 confirmed COVID-19 cases from Wuhan, China were noted in patients with CVD (10.5%), diabetes (7.3%), hypertension (6.0%), all notably higher than the overall case-fatality rate of 2.3% (15). Several smaller cohort studies have yielded similar results suggesting higher risk for adverse events in patients with CVD who contract COVID-19, although biases related to testing and standardized data apply here as well (1,19,(25)(26)(27)(28). Notably, while reports outside of China are limited, data from Italy suggest similar mortality rates and an elevated risk for death in patients with comorbidities (29).…”
Section: Prevalence Of Cvd In Patients With Covid-19supporting
confidence: 51%
“…Increased case-fatality rates in the previously referenced analysis of 44,672 confirmed COVID-19 cases from Wuhan, China were noted in patients with CVD (10.5%), diabetes (7.3%), hypertension (6.0%), all notably higher than the overall case-fatality rate of 2.3% (15). Several smaller cohort studies have yielded similar results suggesting higher risk for adverse events in patients with CVD who contract COVID-19, although biases related to testing and standardized data apply here as well (1,19,(25)(26)(27)(28). Notably, while reports outside of China are limited, data from Italy suggest similar mortality rates and an elevated risk for death in patients with comorbidities (29).…”
Section: Prevalence Of Cvd In Patients With Covid-19supporting
confidence: 51%
“…Similarly, in an analysis of 201 patients with COVID-19, Wu et al found hypertension to have a hazard ratio (HR) of 1.82 (95% CI, 1.13 to 2.95; p ¼ 0.01) for acute respiratory distress syndrome (ARDS) and 1.70 (95% CI, 0.92 to 3.14, p ¼ 0.09) for death. The diabetic patients had a HR of 2.34 (95% CI, 1.35 to 4.05; p ¼ 0.002) for ARDS and HR of 1.58 (95% CI, 0.80 to 3.13, p ¼ 0.19) for death, in a bivariate cox regression analysis [11]. It should be noted however, that neither of these studies were adjusted for all confounding variables.…”
Section: Hypertension As a Prognostic Indicator For Severity And Mortmentioning
confidence: 85%
“…9 Studies have shown that inflammatory cytokines and biomarkers such as interleukin (IL)-2, IL-6, IL-7, granulocyte-colony stimulating factor, macrophage inflammatory protein 1-α, tumor necrosis factor-α, Creactive protein, ferritin, and D-dimer are significantly elevated in those patients with more severe disease. 10 Troponin and N-terminal pro B-type natriuretic peptide (NT-proBNP) can also be elevated. A form akin to hemophagocytic lymphohistiocytosis (sHLH) may occur in patients in this advanced stage of disease.…”
Section: Stage III (Severe) -Systemic Hyperinflammationmentioning
confidence: 99%